2007
DOI: 10.1164/rccm.200707-1088oc
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Phospholipase A2Group X Overexpression in Asthma and Bronchial Hyperresponsiveness

Abstract: Rationale: Secreted phospholipase A 2 enzymes (sPLA 2 s) play key regulatory roles in the biosynthesis of eicosanoids, such as the cysteinyl leukotrienes, but the role of these enzymes in the pathogenesis of asthma is not known. Objectives: To establish if sPLA 2 s are overexpressed in the airways of patients with asthma, and to determine if these enzymes may play a role in the generation of eicosanoids in exercise-induced bronchoconstriction. Methods: Induced sputum samples were obtained from subjects with as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
103
0
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 50 publications
(69 reference statements)
3
103
0
4
Order By: Relevance
“…The levels of GXsPLA 2 , but not GIIA-sPLA 2 , correlated with asthma severity, airway inflammation (sputum neutrophils), and eicosanoid release (BAL fluid prostaglandin E 2 ); greater expression of GX-sPLA 2 compared with other sPLA 2 s (GIIA-sPLA 2 and GV-sPLA 2 ) was also detected in the airway epithelia of the asthmatics (17). We previously found that GX-sPLA 2 was differentially overexpressed in the airway cells (airway epithelial cells and bronchial macrophages) of subjects with asthma and exercise-induced bronchoconstriction compared with other human sPLA 2 s, with further increase in the airways of GX-sPLA 2 in these subjects after exercise challenge (9). Genome-wide expression profiling of this group of asthmatics with exercise-induced bronchoconstriction compared with asthmatic individuals without exercise-induced bronchoconstriction demonstrated that TGM2 (transglutaminase 2) was the gene most differentially expressed at base line between these two groups of asthmatics, with increased expression of TGM2 found in airway epithelial brushing from the asthmatics with exercise-induced bronchoconstriction compared with non-asthmatic control subjects (18).…”
Section: Discussionmentioning
confidence: 76%
“…The levels of GXsPLA 2 , but not GIIA-sPLA 2 , correlated with asthma severity, airway inflammation (sputum neutrophils), and eicosanoid release (BAL fluid prostaglandin E 2 ); greater expression of GX-sPLA 2 compared with other sPLA 2 s (GIIA-sPLA 2 and GV-sPLA 2 ) was also detected in the airway epithelia of the asthmatics (17). We previously found that GX-sPLA 2 was differentially overexpressed in the airway cells (airway epithelial cells and bronchial macrophages) of subjects with asthma and exercise-induced bronchoconstriction compared with other human sPLA 2 s, with further increase in the airways of GX-sPLA 2 in these subjects after exercise challenge (9). Genome-wide expression profiling of this group of asthmatics with exercise-induced bronchoconstriction compared with asthmatic individuals without exercise-induced bronchoconstriction demonstrated that TGM2 (transglutaminase 2) was the gene most differentially expressed at base line between these two groups of asthmatics, with increased expression of TGM2 found in airway epithelial brushing from the asthmatics with exercise-induced bronchoconstriction compared with non-asthmatic control subjects (18).…”
Section: Discussionmentioning
confidence: 76%
“…These higher levels were associated with greater levels of eicosanoids and Th2 cytokines in BALF from PLA 2 R 2/2 mice than from PLA 2 R +/+ mice. Previous animal and human studies showed that sPLA 2 have an important role in the genesis of airway inflammation through the production of proinflammatory eicosanoids in a variety of inflammatory cells (11)(12)(13)(14)(15). Eicosanoids including CysLTs, LTB 4 , and PGD 2 cause lung inflammation directly or indirectly through induction of Th2 cytokines (1)(2)(3)(4).…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies have demonstrated that sPLA 2 -IB and sPLA 2 -X are internalized and degraded via the lysosomal pathway after their binding to PLA 2 R, implicating a possible role of the receptor in the clearance of extracellular sPLA 2 (18)(19)(20)(21)(22). sPLA 2 -IB and sPLA 2 -X are expressed in the lung (11,12,23). The animal study using sPLA 2 -X-deficient mice showed that sPLA 2 -X produced proinflammatory eicosanoids and Th2 cytokines and played a critical role in genesis of allergen-induced airway inflammation (12).…”
mentioning
confidence: 97%
See 2 more Smart Citations